Enhancement of methane production from barley waste - Neves, L. (2006)
Two different approaches were attempted to try and enhance methane production from an industrial waste composed of 100% barley, which results from production of instant coffee substitutes. In previous work, this waste was co-digested with an excess of activated sludge produced in the wastewater treatment plant located in same industrial unit, resulting in a very poor methane yield (25LCH4(STP)/ kgVSinitial), and low reductions in total solids (31%) and in volatile solids (40%). When the barley waste (BW) was subjected to alkaline hydrolysis pre-treatment before co-digestion with activated sludge, the methane production increased to 222LCH4(STP)/kgVSinitial and the total and volatile solids reductions increased to 67% and 84%, respectively. The second approach, followed in the present work, consisted of co-digestion with kitchen waste (40% BW, 60% kitchen waste). The methane production was 363LCH4(STP)/kgVSinitial and the total and volatile solids reductions were 61% and 67%, respectively.